(untitled) (Journal of Applied Learning and Teaching, 2018)
With the increasing adoption of blended (flipped/ hybrid) learning year-by-year this century in higher education, the need for research on the learner experience in blended learning courses is an essential emerging body of literature, but it is one particularly under-represented in Asia. Furthermore, the assumptions emergent from a largely Western milieu investigating mostly Western students in Western University settings need to be tested in an Asian context. Therefore, the purpose of this paper is to understand whether relationships exist between three hitherto well-researched factors - lecturer use of online content in teaching, the students’ ages and students’ understanding of content – and the participation online of working adult students enrolled in a Higher Education Blended course, but crucially one in a Singaporean Higher Education setting. The methodology employs a survey of students (n=1,047) analyzed using the Pearson Chi-Square test of independence. The findings show relationships between all three and student online participation and challenges previously held views that students in high teacher-dependency cultures like Singapore find blended and online learning inferior to traditional modes.